2020
DOI: 10.22146/ajche.60230
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength and Water Absorption of Pavement Derived from Palm Oil Eco Processed Pozzolan (EPP) Material as Partial Cement Replacement

Abstract: Eco Processed Pozzolan (EPP) is derived from Spent Bleaching Earth (SBE) by the calcination process via heat treatment in the palm oil refining industry. EPP can be used as a partial replacement of cement as it contains a high amount of silica and has pozzolanic properties. Besides its properties, the sustainable production of EPP in the palm oil industry, abundantly available, and cheaper raw material have opened an opportunity to explore it as a cement substitute in pavement industries. This research aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Henceforth, this is the first study which focus on stabilization of peat soil that uses eco-processed pozzolan as the main material. Recent study reported by Kusaimi et al [7] also indicates that replacement of cement by EPP with the right percentages will enhance the compressive strength up to 32.4 MPa and lower water absorption of 4.78%. The changes in soil volume are usually concurrent with shrinkage or swelling.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Henceforth, this is the first study which focus on stabilization of peat soil that uses eco-processed pozzolan as the main material. Recent study reported by Kusaimi et al [7] also indicates that replacement of cement by EPP with the right percentages will enhance the compressive strength up to 32.4 MPa and lower water absorption of 4.78%. The changes in soil volume are usually concurrent with shrinkage or swelling.…”
Section: Introductionmentioning
confidence: 85%
“…Pozzolanic materials have been practically used as a substitute for cement. Chindaprasirt et al [6] have established that the use of pozzolan would reduce the use of cement, and Kusaimi et al [7] exemplified by their study, support the idea that the use of EPP as a cement substitute in the manufacture of paving blocks can help to lessen the manufacturing industry's reliance on cement. Eco-processed pozzolan (EPP) is derived from the process of degumming and bleaching crude palm oil waste products from refinery plants and is used in blended cement processing [8].…”
Section: Introductionmentioning
confidence: 90%
“…Various studies have explored the potential utilisation of EPP as a sustainable alternative to cement in different construction applications. Kusaimi et al (2020) conducted a study concentrated on integrating EPP as a cement substitute in pavement blocks. The research aimed to evaluate the performance of pavement blocks formulated with EPP, considering properties such as water absorption and compressive strength.…”
Section: The Strength Analysis Of the Use Of Processed Spent Bleachin...mentioning
confidence: 99%
“…Currently there are research that looked into recycling SBEA for use as partial cement replacement. Part of these research include assessing the pozzolanic properties of SBEA (Rahman et al, 2019) as well as using incorporating it as partial cement replacement in mortar (Rahman et al, 2020), foamed concrete (Rokiah et al, 2019) and road pavement (Kusaimi et al, 2020). These research have shown that SBEA exhibits sufficient pozzolanic properties for use as cement replacement up to 30 %.…”
Section: Introductionmentioning
confidence: 99%